2001
DOI: 10.1046/j.1462-5822.2001.00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Low iron availability modulates the course ofChlamydia pneumoniaeinfection

Abstract: SummaryChlamydiae are obligate intracellular bacteria residing exclusively in host cell vesicles termed inclusions. We have investigated the effects of deferoxamine mesylate (DAM)-induced iron deficiency on the growth of Chlamydia pneumoniae and Chlamydia trachomatis serovar L2. In epithelial cells subjected to iron starvation and infected with either C. pneumoniae or C. trachomatis L2, small inclusions were formed, and the infectivity of chlamydial progeny was impaired. Moreover, for C. trachomatis L2, we obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 37 publications
4
105
0
Order By: Relevance
“…In the literature, the relation between infections and the iron status is very controversial. Some in vitro studies demonstrated that iron deficiency inhibited bacterial proliferation, whereas others indicate that this effect is balanced by numerous alterations of the immune system induced by iron deficiency, such as a decrease in delayed hypersensitivity through abnormalities in lymphocyte transformation, and functional abnormalities of the polymorphonuclear leukocytes (Dallman, 1987;Hallberg & Asp, 1996;Walter et al, 1997;Al-Younes et al, 2001). However, the latter studies investigated iron deficiency with anemia.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the relation between infections and the iron status is very controversial. Some in vitro studies demonstrated that iron deficiency inhibited bacterial proliferation, whereas others indicate that this effect is balanced by numerous alterations of the immune system induced by iron deficiency, such as a decrease in delayed hypersensitivity through abnormalities in lymphocyte transformation, and functional abnormalities of the polymorphonuclear leukocytes (Dallman, 1987;Hallberg & Asp, 1996;Walter et al, 1997;Al-Younes et al, 2001). However, the latter studies investigated iron deficiency with anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking iron uptake by infected cells inhibits the growth of these pathogens [29][30][31][32][33] . To access host-derived iron sources, these bacteria exploit specific intracellular niches in the host cell.…”
Section: Siderophoresmentioning
confidence: 99%
“…Bacterial infection (S. enteritidis) increases cytokine mRNA levels in enterocyte-like Caco-2 human intestinal cells, an increase that was further enhanced with higher Fe concentration (Foster et al, 2001). An elevated Fe status is known to increase the susceptibility to various infections (Al-Younes et al, 2001;Foster et al, 2001;Lounis et al, 2001;Weinberg, 1999;Weiss, 2002). Moreover, Fe accumulation in the liver in human hepatitis C virus infection is associated with an impaired response to IFNα therapy and with faster progression of the disease (Weiss, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Results indicate, however, that C. pneumoniae is dependent on Fe for its growth (Al-Younes et al, 2001;Freidank et al, 2001), and that a greater availability of Fe increases the virulence of S. enteritidis bacteria (Foster et al, 2001) and stimulates the growth of M. tuberculosis (Serafin-Lopez et al, 2004). From data in S. enteritis infected Caco-2 cells it has been suggested that an elevated enterocyte Fe status increases the susceptibility to infection and exacerbates the mucosal inflammatory response because of increased cytokine expression (Foster et al, 2001).…”
Section: Effects Of Xenobiotics On Host Resistancementioning
confidence: 99%
See 1 more Smart Citation